The Power of Principles : physics revealed : A Conversation with Nima Arkani-Hamed. - Burton, Howard (Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Nima Arkani-Hamed, faculty member at the renowned Institute for Advanced Study in Princeton. Nima Arkani-Hamed is one of today's leading particle physicists. In this wide-ranging Ideas Roadshow conversation, Nima discusses how we discover the laws of nature, the ""scientific method"", the relation between theory and experiment and how we can push our understanding well beyond where experiments can currently reach. With his unbridled enthusiasm and engaging eloquence, Nima takes us inside the world of a working theo.
Description based upon print version of record.
Keywords: Arkani-Hamed, Nima -- Interviews.; Science -- Methodology.; Communication in physics.; Sciences -- Méthodologie.; Communication en physique.; Astrophysics.; Physics.; SCIENCE.; Cosmology.; Relativity.; Communication in physics; Science -- Methodology; Interviews